2021
DOI: 10.1021/jacs.1c05949
|View full text |Cite
|
Sign up to set email alerts
|

Packing Biomolecules into Sierpiński Triangles with Global Organizational Chirality

Abstract: Fractals are found in nature and play important roles in biological functions. However, it is challenging to controllably prepare biomolecule fractals. In this study, a series of Sierpinśki triangles with global organizational chirality is successfully constructed by the coassembly of L-tryptophan and 1,3-bi(4-pyridyl)benzene molecules on Ag(111). The chirality is switched when replacing L-tryptophan by D-tryptophan. The fractal structures are characterized by low-temperature scanning tunneling microscopy at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…In the past decade, the construction of Sierpiński triangles (STs) on surfaces has attracted increasing attention due to their aperiodic but ordered structures that give them specific mechanical, optical, electronic, and magnetic properties. Theoretical predictions have revealed that the combination of threefold and 120° V-shaped molecules with terminal interaction centers is the general prerequisite to create STs; , this is corroborated by a pioneering experimental study of Wu et al . Subsequently, a variety of molecular-based STs have been achieved on metal surfaces by noncovalent (e.g., coordination bonds and hydrogen bonds , ) and covalent bonding interactions. More recently, an important development reported by Wang et al detailed the construction of ST-derived MONs on a Au(111) surface …”
Section: Introductionmentioning
confidence: 96%
“…In the past decade, the construction of Sierpiński triangles (STs) on surfaces has attracted increasing attention due to their aperiodic but ordered structures that give them specific mechanical, optical, electronic, and magnetic properties. Theoretical predictions have revealed that the combination of threefold and 120° V-shaped molecules with terminal interaction centers is the general prerequisite to create STs; , this is corroborated by a pioneering experimental study of Wu et al . Subsequently, a variety of molecular-based STs have been achieved on metal surfaces by noncovalent (e.g., coordination bonds and hydrogen bonds , ) and covalent bonding interactions. More recently, an important development reported by Wang et al detailed the construction of ST-derived MONs on a Au(111) surface …”
Section: Introductionmentioning
confidence: 96%
“…14,15 For example, lowtemperature scanning tunneling microscopy was combined with the density functional theory (DFT) calculations to study packing biomolecules with the chiral Sierpinski triangle structure. 16 Lignin is an atypical plant macromolecule composed of aromatics. Gaining an insight into its 3D structure and formation is important for an efficient conversion of this renewable feedstock to resins, carbon fibers, commodity chemicals, and fuels.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Surface chirality is an area of growing interest, due to its intriguing scientific significance and many potential applications, such as chiral sensors, circularly polarized light emission, enantioselective separation, crystallization, and catalysis. In addition to the well-known molecular chirality, surface chirality can also arise from achiral molecules, as certain absorbed conformations induce chirality. , A less studied form of surface chirality is organizational chirality, which arises solely from the arrangement of the molecules on the surface . Therefore, both chiral , and achiral molecules , have been utilized to form organizational chiral structures. Current means to produce organizational chirality primarily rely on self-assembly, from simple and small organic molecules ,, to large aromatic ones. , The resulting chiral structures are restricted to those driven by the resulting intermolecular and molecule–surface interactions.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 A less studied form of surface chirality is organizational chirality, which arises solely from the arrangement of the molecules on the surface. 7 Therefore, both chiral 8,9 and achiral molecules 7,10−14 have been utilized to form organizational chiral structures. Current means to produce organizational chirality primarily rely on selfassembly, from simple and small organic molecules 7,9,15 to large aromatic ones.…”
Section: ■ Introductionmentioning
confidence: 99%